Retenção de água em classes de solos no oeste potiguar - Silva, Antonio Carlos da (Universidade Federal Rural do Semi-Árido, 2018)
The soil structure from the point of view of physics is a dynamic attribute, influenced by genetic conditions and anthropic changes that require an integrated approach. The retention curve is one of the main tools used for this purpose. In this sense, the objective of this work was to evaluate structural relationships in soil classes, associated to the chemical attributes in agroecosystems in the Terra de Esperança Land Settlement Project in Governador Dix Sept Rosado-RN aiming at distinguishing the environments. Deformed and undisturbed samplings were collected in 10 profiles, in their respective horizons, which classes of soils involved: Haplustepts, Eutrustox, Calciustolls, Usticfluvents. The analysis consisted of physical attributes, including granulometry, Ds, PT det and aeration, macroporosity and microporosity, CC, PMP, AD, and consequently the water retention curve in soil and chemicals, being CE, pH, and the macronutrients (P, K+, Na+, Ca2+, Mg2+) and (H+Al), PST and TOC. The results were expressed by the average of four replicates per horizon, in the respective classes for the analyzed attributes, through the multivariate analysis. It was the main tool used to detect the most sensitive attributes in the environment distinction. Physicochemical attributes of the different soil classes were determinant in distinguishing the environments, their local characteristics and particularities, as well as the inorganic fractions, in particular silt and clay, reflecting in microporosity, aeration porosity and water available. In the class of Calciustolls, the origin material influenced in the physical and chemical attributes in function of the predominance of the silt fraction, whereas, the clay was determinant for classes of Haplustepts and Usticfluvents, as for the sand fraction in surface and clay in the horizon (Bw) for the Eutrustox. Regarding the expressiveness of the grouped physical attributes, Ds, CC, AD, PMP, U, θ, P, aeration and macroporosity stood out. For the most sensitive chemical attributes in the differentiation are included the Calciustolls with the variables: PST, Na+ and CE. Eutrustox with (H+Al) and Al3, and Haplustepts and Usticfluvents: : pH, K+, P, COT, Ca2+, SB and T
Keywords: Água no solo; Estruturação; Semiárido; Vegetação nativa; Water in soil; Structuring; Semiarid; Native vegetation; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO